SonicWALL secure wireless network integrated solutions guide - Levy, Joe. (Burlington, Mass. : Syngress, 2008)
Nearly forty percent of the world's 1 billion+ Internet users are wireless. It's a truly staggering fact to think that the majority of these wireless implementations are fundamentally insecure, leaving users and private data at risk. Many wireless proprietors think that the convenience of wireless outweighs the possible risk of insecure impelentation, or that secure wireless is far too complicated to worry about deploying. SonicWALL® Secure Wireless Networks Integrated Solutions Guide provides a systematic approach to creating secure wireless networks, using the Plan, Design, Implement, and Optimize model. This introduction to wireless network security is both comprehensive and easy to understand. Using straightforward language, this book describes deployment best practices, what SonicWALL security appliances do, and how they interoperate within an existing or new network. It begins with brief overviews of the theory of risk management, the history of wireless networks, and today's top five wireless threats. Real-world case studies highlight wireless solution business drivers for education, healthcare, retail and hospitality, and government agencies, as well as their respective regulatory compliance requirements. SonicWALL believes that the days of being forced to accept inherent risk in wireless networking are over. By using modern security standards and sound network design methods, your wireless network should be just as secure as your wired network. Wireless networks can be made as secure as wired networks, and deploying this type of security can be far less complicated than you think. In this book, and through their massive product offerings, SonicWALL gives you (the secure wireless network hopeful) all of the planning, implementation, and optimizing tools you need to do wireless. Securely. * Official guide from SonicWALL * Written by SonicWALL engineers and documentation specialists * Appropriate for all audiences, from the small proprietor to the enterprise IT specialist * A complete reference to plan, design, implement, and optimize a secure wireless network with SonicWALL's extensive wireless product offerings.
Preface -- Using This Book -- Part 1: Planning -- Chapter 1: Introduction to Secure Wireless Networking -- Chapter 2: Planning Wireless Access Deployments -- Chapter 3: Creating and Defining a Network Security Policy -- Chapter 4: Wireless Solutions for Vertical Markets -- Part 2: Designing -- Chapter 5: SonicWALL Products Solutions Library -- Chapter 6: Three Phases for a Secure Wireless Network -- Chapter 7: Designing for User Segmentation -- Part 3: Implementing -- Phase 1: Deploying the UTM Gateway -- Chapter 8: Configuring SonicWALL UTM Gateway Appliances -- Chapter 9: Configuring User Segmentation -- Chapter 10: Configuring Distributed Wireless Devices -- Chapter 11: Configuring Wireless Guest Services for Hotspots -- Chapter 12: Configuring Virtual Access Points -- Chapter 13: Configuring RF Monitoring and Protection -- Phase 2: Deploying Secure Remote Access Solutions -- Chapter 14: Configuring Secure Remote Access Solutions -- Phase 3: Deploying Centralized Management Solutions -- Chapter 15: Configuring SonicWALL Global Management System -- Part 4: Optimizing -- Chapter 16: Optimizing Your Secure Wireless Network -- Appendix A: Configuring External Authentication Servers -- Appendix B: SonicWALL Knowledge Check -- Appendix C: Answers to SonicWALL Knowledge Check -- Bibliography -- Index.
Includes bibliographical references (p. [463]-470) and index.
Keywords: Firewalls (Computer security); Wireless LANs -- Security measures; Electronic books